Keberadaan Bahan Amorf dan Hubungannya dengan Sifat Kimia Andisol di Kecamatan Ponjong, Gunung Kidul, - Ratnahadi, Faesol (SEKOLAH PASCA SARJANA UGM, 2005)
ABSTRACT This study was conducted at three locations, namely: Gadung, Gangsir and Gatel with elevation of 460,300 and 450 m above sea level, respectively. The locations were situated at karst formation of Ponjong Gunung Kidul Province of Jogjakarta. The objectives of this research were to find out the existence, quantity, type of amorph materials in andisols and its correlation to the chemical properties. Identification of amorph materials were supported by data of soil chemical properties, differential thermal analysis (DTA) and Infra-red spectral. Soil samples were taken from each layer of soil profiles, as representatives of surface and subsurface soil, respectively. The soil chemical analysis was conducted at Soil Science Laboratory of Gadjah Mada University, and clay mineralogy analysis was done at soil science laboratory of Bogor Agriculture University. Application of selective dissolution technique was supported by infra-red spectral and differential thermal analysis used to identify the existence of the amorph materials in the soil, such as: allophane, imogolit, ferrihydrit, and sesquioxide. The content of allophane-imogolite was so various, the highest one was found at eastern side of Gadung, while the lowest one was found at western side of Gangsir. The results of chemical analysis indicated that the soil posses an andic properties such as phosphate retention > 85%, pH-NaF > 10, CEC > 24 me%, C-organic > 6%, and (Alo+1/2Feo)at range of 1.3-2.62. Infrared spectral showed four major regions, namely: 3445, 1650, 910-1029 and 430-543 cm-1. The maximum band absorption was derived to OH vibration, H-O-H deformation, Si-O-Al bond, condensed Si-O, respectively. Thermal characteristic showed endothermic peak at 50-150 oC and exothermic peak at 800-950 oC.